(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This paper explores the method of virtual ethnography in social research and aims to provide a general understanding of this method, focusing on its foundations and methodological procedures. Although several social research continuously discuss the importance of virtual ethnography, this research method still requires more attention compared to other methods, especially regarding methodological procedures. This paper discusses virtual ethnography by focusing on a brief review of the evolution of ethnography from traditional to virtual, its relationship with some related concepts, its concept, and its basic principles, in addition to addressing the procedures of virtual ethnographic research, and concludes with a review of some ethical challenges, as well as the main difficulties and advantages of virtual ethnographic research.